Apostolat miłosierdzia bł. Edmunda Bojanowskiego w świetle zasady godności człowieka - Stolarczyk, Ireneusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The apostolate of mercy of Blessed Edmund Bojanowski is a work of love outside the time period of the life of the Blessed. Timelessness of works of mercy makes that till nowadays his look at the other people, taking into account the concern of every man and effective participation in the development of the whole man is the theme of many apostolic initiatives. Blessed E. Bojanowski was able to see Christ in another man; he could also love Christ in another man. All this has become the force of timelessness of his initiatives to help others through the richness of works of mercy. This work shows the works of mercy of the Blessed as an act of service to respect the dignity of each and every human being. The first part introduces the understanding of the principle of human dignity in a supernatural and natural dimension. The second part shows the timeless efficacy of the works of mercy of Blessed Edmund in preserving and restoring the dignity of every person’s life. It should be noted that the fruitfulness of the works of the apostolate of mercy is an important contribution to building a social order.